Hypodontia in primary dentition: A case report - Cunha, Robson Frederico [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Hirata, Edo [UNESP]; Toyota, Edna (My University, 1999)
The prevalence, possible etiological factors and management of hypodontia in primary dentition are reviewed. A case of hypodontia involving the primary lower incisor is reported.
Keywords: case report; dentition; human; hypodontia; infant; male; pathology; Anodontia; Dentition, Primary; Humans; Infant; Male